2015
DOI: 10.1093/jamia/ocv096
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive analysis of medication errors reported to the Egyptian national online reporting system during six months

Abstract: There are common problems among different healthcare systems, so that sharing experiences on the national level is essential to enable learning from MEs. Internationally, there is a great need for standardizing ME terminology, to facilitate knowledge transfer. Underreporting, inaccurate reporting, and a lack of reporter diversity are some limitations of this study. Egypt now has a national database of MEs that allows researchers and decision makers to assess the problem, identify its root causes, and develop p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 6 publications
3
40
3
Order By: Relevance
“…Prescribing errors were the most frequent MEs. This is in agreement with many studies conducted in Middle East countries [25][26][27][28][29][30][31][32][33][34][35][36] .…”
Section: Effect Of Mean Number Of Medication Errors Onsupporting
confidence: 93%
“…Prescribing errors were the most frequent MEs. This is in agreement with many studies conducted in Middle East countries [25][26][27][28][29][30][31][32][33][34][35][36] .…”
Section: Effect Of Mean Number Of Medication Errors Onsupporting
confidence: 93%
“…The Egyptian (ME) reporting system, disclosed that the most frequent administration errors were extra dose, dose omission, and medication omission. 27 Many interesting explanations have been trying to clarify this frequency order in NICU. Starting with the wrong dose, drugs are usually found in the unit dose for adults (e.g.1 vial, 1 ampoule equals 1 adult dose).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the Egyptian (ME) reporting system displayed that the most common causes reported were lack of knowledge and experience, environmental factors (e. g. work overload and diversions), deficiency of drug information sources, and incomplete prescribing commands. 27 Rates of reported errors calculated from voluntary self-reported data are usually biased because of the selective or underreporting, but, it reflects the state of science and provides valuable information for designing effective interventions to reduce neonatal harm risk. 28 Limited generalizability of results due to the small sample of NICU nurses at Cairo University Pediatric hospital, resulted in a limited diversity of reporting NICU nurses in addition to inter-individual differences in assessment of error outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, there are a trend from the governmental health sector to enhance processing system of medication therapy ,drug items and medication prescription [1].Egypt is one of the most populous countries in middle east [2] and there are a massive number of paper based-prescriptions are issued and dispensed annually for free to patients. Previous studies have revealed problems related to paper prescriptions in Egypt [3]. Improper prescribing can cause harm for patients and will be waste of money and time [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, many papers have been published on paper-based prescription highly rate errors [3][6] [7].different methods for the optimal prescribed items in pharmacies have been proposed [8] [9]. Updated databases have to be maintained in order to extract useful information and also tracking error existence.…”
Section: Introductionmentioning
confidence: 99%